2019
DOI: 10.1101/623512
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of artificially introduced Enterococcus faecalis strains in experimental necrotizing enterocolitis

Abstract: Enterococcus faecalis is a ubiquitous intestinal symbiont and common early colonizer of the neonatal gut. Although colonization with E. faecalis has been previously associated with decreased NEC pathology, these bacteria have been also implicated as opportunistic pathogens. Here we characterized 21 strains of E. faecalis, naturally occurring in 4-day-old rats, for potentially pathogenic properties and ability to colonize the neonatal gut. The strains differed in hemolysis, gelatin liquefaction, antibiotic resi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The remaining case has a microbiota dominated by enterococci, which lack the potential to stimulate TLR4 via LPS, and are not amongst the extreme low-CpG organisms. This effect may be species or strain speci c as rodent models have demonstrated that certain strains of Enterococcus faecalis are protective against NEC, whilst other strains are associated with the development of NEC [18]. This case may therefore represent a separate aetiology that is not widely represented in our cohort.…”
Section: Discussionmentioning
confidence: 95%
“…The remaining case has a microbiota dominated by enterococci, which lack the potential to stimulate TLR4 via LPS, and are not amongst the extreme low-CpG organisms. This effect may be species or strain speci c as rodent models have demonstrated that certain strains of Enterococcus faecalis are protective against NEC, whilst other strains are associated with the development of NEC [18]. This case may therefore represent a separate aetiology that is not widely represented in our cohort.…”
Section: Discussionmentioning
confidence: 95%